FCGR3B copy number variation is associated with susceptibility to systemic, but not organ-specific, autoimmunity. - Fanciulli, M; Norsworthy, P; Petretto, E; Dong, R; Harper, L; Kamesh, L; Heward, J; Gough, S; de Smith, A; Blakemore, A; Froguel, P; Owen, C; et al. (2007)
Naturally occurring variation in gene copy number is increasingly recognized as a heritable source of susceptibility to genetically complex diseases. Here we report strong association between FCGR3B copy number and risk of systemic lupus erythematosus (P = 2.7 x 10(-8)), microscopic polyangiitis (P = 2.9 x 10(-4)) and Wegener's granulomatosis in two independent cohorts from the UK (P = 3 x 10(-3)) and France (P = 1.1 x 10(-4)). We did not observe this association in the organ-specific Graves' disease or Addison's disease. Our findings suggest that low FCGR3B copy number, and in particular complete FCGR3B deficiency, has a key role in the development of systemic autoimmunity.